Alterations in plasma proteome during acute COVID-19 and recovery - Maciej Suski; Agnieszka Olszanecka; Aneta Stachowicz; Anna Kiepura; Michał Terlecki; Józef Madej; Marek Rajzer; Rafał Olszanecki (BMC, 2024)
Abstract Background The severe course of COVID-19 causes cardiovascular injuries, although the mechanisms involved are still not fully recognized, linked, and understood. Their characterization is of great importance with the establishment of the conception of post-acute sequelae of COVID-19, referred to as long COVID, where blood clotting and endothelial abnormalities are believed to be the key pathomechanisms driving circulatory system impairment. Methods The presented study investigates temporal changes in plasma proteins in COVID-19 patients during hospitalization due to SARS-CoV-2 infection and six months after recovery by targeted SureQuant acquisition using PQ500 panel. Results In total, we identified 167 proteins that were differentially regulated between follow-up and hospitalization, which functionally aggregated into immune system activation, complement and coagulation cascades, interleukins signalling, platelet activation, and extracellular matrix organization. Furthermore, we found that temporal quantitative changes in acute phase proteins correlate with selected clinical characteristics of COVID-19 patients. Conclusions In-depth targeted proteome investigation evidenced substantial changes in plasma protein composition of patients during and recovering from COVID-19, evidencing a wide range of functional pathways induced by SARS-CoV-2 infection. In addition, we show that a subset of acute phase proteins, clotting cascade regulators and lipoproteins could have clinical value as potential predictors of long-term cardiovascular events in COVID-19 convalescents.